Superior Chemical Sensing Performance of Black Phosphorus: Comparison with MoS2 and Graphene. Issue 32 (10th June 2016) - Cho, Soo‐Yeon; Lee, Youhan; Koh, Hyeong‐Jun; Jung, Hyunju; Kim, Jong‐Seon; Yoo, Hae‐Wook; Kim, Jihan; Jung, Hee‐Tae
Abstract : Superior chemical sensing performance of black phosphorus (BP) is demonstrated by comparison with MoS2 and graphene. Dynamic sensing measurements of multichannel detection show that BP displays highly sensitive, selective, and fast‐responsive NO2 sensing performance compared to the other representative 2D sensing materials.